Pengaruh Hukum Adat terhadap Hukum Kewarisan Islam di Indonesia - Maman Suparman; Andi Achmad Zulkarnaen (Advokasi Hukum & Demokrasi (AHD), 2024)
Islamic law experts since classical times have actually been aware of the problem of the influence of customary law on Islamic law. Even though they do not view custom as an independent source of law, these legal experts still recognize the effectiveness of custom in the process of legal interpretation. In the methodology of Islamic law (ushul al-fiqh), custom ('uruf/adah) is accepted as a source of law developed from the rational mind (ra'yu) in addition to qiash, ikhtihsan and istislah. In other words, customary law has a place in Islamic law as long as it does not conflict with the sources of revealed law, namely the Qur'an and Hadith. Acceptance of customs on the basis of public benefit is always considered a necessity for operating the Islamic legal system which is always required to be able to reconcile various interests and solve problems that arise in society and far from the birthplace of the Islamic legal system. This journal writing uses a normative juridical approach method. With the result that a harmonious relationship between Islamic law and customary law had existed long before the Dutch colonialists set foot on the archipelago. Dutch colonial legal politicians who always sharply contrasted Islamic law with customary law were not supported by the realities of society.